Jordan Economic Monitor, Fall 2017 : Towards Stronger External Trade Performance - World Bank (World Bank, Washington, DC, 2017)
Jordan's economic performance remains tempered in 2017 while the fiscal adjustment is in progress; yet there are positive signs on the horizon. Real GDP growth for 2017 is expected to reach 2.1 percent, just a 0.1 percentage point (pp) increase from 2016. On the supply side, services continue to be the principal driver of GDP growth, and these are propelled by a robust performance in tourism. Jordan's industrial sector is expected to regain momentum based on a recovery in mining and quarrying as the effect of the drop in potash prices starts dissipating. On the demand side, private consumption and investment in addition to net exports of goods and services are projected to lead GDP growth. The combination of public consumption and public investment are expected to be a drag on GDP growth. The reliance of GDP growth on private demand, as opposed to public demand, is a welcomed change from growth patterns since 2014. As a result of the progress in net exports, the current account deficit is projected to narrow slightly to 8.8 percent of GDP.